1968
DOI: 10.1021/ja01026a038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ozonation reactions. III. Ethers

Abstract: A study of the mechanism of the ozonation of ethers has been carried out utilizing isotope effect rate studies, competitive relative rate studies on various classes of ethers, and product analysis of ozonations using ozone-oxygen and ozone-nitrogen streams. Results are discussed in terms of both the mode of initial attack of ozone on the system and the varieties of decomposition available to the hydrotrioxide intermediate I. The over-all mechanism is a complicated one involving free radical autoxidation when o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1971
1971
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 2 publications
0
14
0
2
Order By: Relevance
“…The authors mentioned the formation of alcohols, aldehydes, ketones and esters with production of hydrogen peroxide and molecular oxygen. Erickson et al (1968) identified tert-butyl acetate, tert-butyl formate and tert-butyl alcohol as ETBE ozonation byproducts. According to Bailey and Lerdal (1978), two types of initial attack of ozone on ethers take place and lead to the formation of hydrotrioxide intermediates (identified by Stary et al, 1976).…”
Section: And the Year 2000 By A Quadrupling Of The American Consumptmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors mentioned the formation of alcohols, aldehydes, ketones and esters with production of hydrogen peroxide and molecular oxygen. Erickson et al (1968) identified tert-butyl acetate, tert-butyl formate and tert-butyl alcohol as ETBE ozonation byproducts. According to Bailey and Lerdal (1978), two types of initial attack of ozone on ethers take place and lead to the formation of hydrotrioxide intermediates (identified by Stary et al, 1976).…”
Section: And the Year 2000 By A Quadrupling Of The American Consumptmentioning
confidence: 99%
“…Studies on the ozonation of ethers were conducted mainly in organic solvents between -80°C and room temperature (Price and Tumolo, 1964;Erickson et al, 1968;Bailey and Lerdal, 1978). The authors mentioned the formation of alcohols, aldehydes, ketones and esters with production of hydrogen peroxide and molecular oxygen.…”
Section: And the Year 2000 By A Quadrupling Of The American Consumptmentioning
confidence: 99%
“…Antiperiplanar lone pairs will elongate the C-H bond as well as stabilize the incipient dioxonium ion. The 1,3-diplolar insertion mechanism (Scheme 3b) has been postulated for the ozonation of ethers (10)(11)(12), aldehydes (13,14), and hydrocarbons (15,16). Ozone attack on oxygen (Scheme 3c) is similar to that proposed for the ozonation of certain amines (18), and ethers (12).…”
Section: Substituent Effectsmentioning
confidence: 99%
“…Ozon zeigt bei tiefer Temperatur Einschiebungsreaktionen in CH-Bindungen. Ffir DiisopropylMher (= RH) und Isopropanol wurde die Bildung von bei -80 ~ noch stabilen Trioxiden mit drei aneinandergeknfipften O-Atomen vermutet [29][30][31][32]: Das unterschiedliche mechanistische Verhalten mit der Konzentration ist nur mit Typ F12 vereinbar, der zweite Schritt k6nnte mindestens zwei Schritte unterschiedlicher Ordnung aufweisen. Dies wfirde auch die Konzentrationsabhfingigkeit der W/irmet6nung erklgren.…”
Section: Ozonisation Yon Diisopropyl~ither Und Isopropanolunclassified
“…3). Diese Befunde deuten auf die Bildung eines analogen Trioxids in viel schlechterer Ausbeute, was auch aufgrund der Ergebnisse mit anderen Untersuchungsmethoden vermutet wurde [30][31][32][33]. Der zweite Peak entspricht nahezu einer Reaktion erster Ordnung.…”
Section: Ro + Ro2 (Ro)20 (18)unclassified